2017
DOI: 10.1089/sur.2017.028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Standardized Protocol of Antibiotic Therapy on Surgical Site Infection after Laparoscopic Surgery for Complicated Appendicitis

Abstract: In patients undergoing laparoscopic surgery for complicated appendicitis, five days of cefuroxime and metronidazole did not lead to more SSIs, and it decreased the medical costs compared with non-standardized antibiotic regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…A total of fifty studies were identified after the search, and the abstracts of these articles were reviewed. Only five full text articles were found to be pertinent to the review after methodological assessment (1 RCT 14 , 4 cohort studies 8,9,15,16 ). Figure 1 shows the process of identification, screening, and inclusion of studies in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of fifty studies were identified after the search, and the abstracts of these articles were reviewed. Only five full text articles were found to be pertinent to the review after methodological assessment (1 RCT 14 , 4 cohort studies 8,9,15,16 ). Figure 1 shows the process of identification, screening, and inclusion of studies in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence-based guidelines for antibiotic treatment of complicated appendicitis recommend the administration of antibiotics for 5-7 days after surgery to reduced wound and organ-space infections. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Although variability exist on the timing of sequential therapy, most studies showed that after at least 24 hours of intravenous antibiotic therapy, shifting to oral antibiotic therapy is safe once the patient has improvement in clinical parameters such as absence of fever, decreasing leukocytosis, and return of normal gastrointestinal function. 1,2 However, a study on shortened antibiotic treatment showed no significant difference in infectious complications between a two-day course of antibiotic treatment and a four-day course of antibiotic treatment among patients with complicated intra-abdominal infections after their index sourcecontrol procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, several studies' findings were influenced by the expertise and skill of surgeons 17 . For many treatments, including cholecystectomy, laparoscopic surgery has lately acquired widespread acceptability because it provides advantages like reduced scarring, less pain, and an earlier return to normal activities 18 . The first LA was carried out by German gynaecologist Semm in 1981 19 .…”
Section: Discussionmentioning
confidence: 99%